2015
DOI: 10.1371/journal.pone.0145995
|View full text |Cite
|
Sign up to set email alerts
|

KPU-300, a Novel Benzophenone–Diketopiperazine–Type Anti-Microtubule Agent with a 2-Pyridyl Structure, Is a Potent Radiosensitizer That Synchronizes the Cell Cycle in Early M Phase

Abstract: KPU-300 is a novel colchicine-type anti-microtubule agent derived from plinabulin (NPI-2358). We characterized the effects of KPU-300 on cell cycle kinetics and radiosensitization using HeLa cells expressing the fluorescent ubiquitination-based cell cycle indicator (Fucci). Cells treated with 30 nM KPU-300 for 24 h were efficiently synchronized in M phase and contained clearly detectable abnormal Fucci fluorescence. Two-dimensional flow-cytometric analysis revealed a fraction of cells distinct from the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The loose attachment of cells to dishes during mitosis allows M-phase cells to be selectively detected by the shake-off method [1][2][3] , with quite a high purity (> 90%), which has been used in a wide range of studies 16,17 . However, sustainability of the synchronicity was not fully investigated.…”
Section: Validation Of Sustainability Of Synchronicity In Hela-fucci mentioning
confidence: 99%
“…The loose attachment of cells to dishes during mitosis allows M-phase cells to be selectively detected by the shake-off method [1][2][3] , with quite a high purity (> 90%), which has been used in a wide range of studies 16,17 . However, sustainability of the synchronicity was not fully investigated.…”
Section: Validation Of Sustainability Of Synchronicity In Hela-fucci mentioning
confidence: 99%
“…The radioprotectant effect of hypoxia (healthy, oxygenated cells surrounding the tumor are more sensitive to ionizing radiation than those targeted by RT) and other radio-resistance factors can be reduced or even eliminated by introducing radiosensitizers, i.e., substances that sensitize cells to radiation [3][4][5]. Various radiosensitization strategies are also being developed, e.g., Okuyama et al reported that HeLa cells could be synchronized in early M-phase after treatment with a novel anti-microtubule agent, KPU-300, consequently leading to significant synergistic decrease of surviving fraction after the subsequent radiation exposure [6]. Due to the fact that the number of radiosensitizers employed in clinics is surprisingly small, it seems rational to look for and test new potentially radiosensitizing molecules.…”
Section: Introductionmentioning
confidence: 99%
“…While the mono-alkylidene natural product 3 has been prepared several times, 7 medicinal chemistry and the structure-activity relationships were advanced using bis-alkylidene derivatives. 8 This structural modification not only improved stability and enhanced the tubulin-stabilizing bioactivity but also greatly simplified the synthesis and enabled rapid generation of many unsaturated non-natural amino acid derivatives for evaluation. The construction of bis-alkylidene DKP structures is now well established and can be easily accomplished through iterative aldol condensations using bisacetoxyglycine anhydride (5) and aromatic aldehydes (see Fig.…”
Section: Introductionmentioning
confidence: 99%